Adjunct interventions to standard medical management of buprenorphine in outpatient settings: A systematic review of the evidence. (1st November 2021) - Wyse, Jessica J.; Morasco, Benjamin J.; Dougherty, Jacob; Edwards, Beau; Kansagara, Devan; Gordon, Adam J.; Korthuis, P. Todd; Tuepker, Anaïs; Lindner, Stephan; Mackey, Katherine; Williams, Beth; Herreid-O'Neill, Anders; et al.
Highlights: Systematic review adjunctive interventions with standard medical management of buprenorphine. Identified psychosocial (14), complementary (2), tech. (3), structural (1) interventions. No evidence adding psychosocial interventions to SMM improves patient outcomes. Need for research identifying supportive adjunctive interventions. Policy implications discussed; active research summarized. Abstract: Background: A growing body of research has examined adjunctive interventions supportive of engagement and retention in treatment among patients receiving buprenorphine for opioid use disorder (OUD). We conducted a systematic review of the literature addressing the effect on key outcomes of adjunctive interventions provided alongside standard medical management of buprenorphine in outpatient settings. Methods: We included prospective studies examining adults receiving buprenorphine paired with an adjunctive intervention for the treatment of OUD in an outpatient setting. Data sources included Medline, Cochrane Central Register of Controlled Trials, CINAHL and PsycINFO from inception through January 2020. Two raters independently reviewed full-text articles, abstracted data and appraised risk of bias. Outcomes examined included abstinence, retention in treatment and non-addiction-related health outcomes. Results: The final review includes 20 manuscripts, 11 randomized control trials (RCTs), three secondary analyses of RCTs and six observational studies. Most studies examined psychosocial interventions (n = 14). Few examined complementary therapies (e.g., yoga; n = 2) or technological interventions (e.g., electronic pill dispensation; n = 3); one study examined an intervention addressing structural barriers to care (patient navigators; n = 1). Low risk of bias RCTs found no evidence that adding psychosocial interventions to buprenorphine treatment improves substance use outcomes. Conclusions: Research is needed to identify adjunctive interventions with potential to support medication adherence and addiction-related outcomes for patients engaged in buprenorphine treatment. Data from clinical trials suggest that lack of ready access to psychosocial treatments should not discourage clinicians from prescribing buprenorphine.